2018
DOI: 10.1016/j.juro.2017.11.074
|View full text |Cite|
|
Sign up to set email alerts
|

Defining a Cohort that May Not Require Repeat Prostate Biopsy Based on PCA3 Score and Magnetic Resonance Imaging: The Dual Negative Effect

Abstract: In patients with dual negative tests (multiparametric magnetic resonance imaging and PCA3 score) clinically significant prostate cancer was never found on biopsy, which may be unnecessary in this group. This study was limited by its retrospective design, selection bias and lack of cost-effectiveness data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Others have attempted to use prostate biomarkers in combination with mpMRI to enhance the accuracy for predicting GR [7,15,25,26]. For example, Lai et al [7] found that the combination of mpMRI and PSAD when added to other clinical parameters yielded an AUC of 0.84, which was significantly greater than either mpMRI alone (AUC 0.74) or PSAD alone (AUC 0.77).…”
Section: Discussionmentioning
confidence: 99%
“…Others have attempted to use prostate biomarkers in combination with mpMRI to enhance the accuracy for predicting GR [7,15,25,26]. For example, Lai et al [7] found that the combination of mpMRI and PSAD when added to other clinical parameters yielded an AUC of 0.84, which was significantly greater than either mpMRI alone (AUC 0.74) or PSAD alone (AUC 0.77).…”
Section: Discussionmentioning
confidence: 99%
“…However, patient selection methods based on risk calculators cannot localize csPCa within the gland, which may be missed by systematic biopsy. Diagnostic yields of biopsy procedures can be increased by using imaging to refine patient selections [20][21][22][23], and thereafter to direct biopsies to suspicious locations, thus reducing the number of men undergoing biopsy and consequently overtreatments of men with insignificant disease [24]. Central to these developments are the emerging roles of multiparametric magnetic resonance imaging (mpMRI) and MR-directed biopsy (MRDB; refers to all biopsy methods using prior mpMRI information) for PCa diagnosis and treatment selection.…”
Section: Addressing Clinical Needs In Pca Diagnosismentioning
confidence: 99%
“…Perlis and colleagues presented results based on 128 nonsuspicious mpMRIs. No patient with a non-suspicious mpMRI and a normal PCA3 score had significant cancer on biopsy (NPV=100% (p <0.0001)) [37]. Gnanapragasam and colleagues reported the results of a PHI test combined with a non-suspicious mpMRI in 94 patients.…”
Section: Biomarkers and Risk Calculatorsmentioning
confidence: 99%